Antibiotic use in children before and after an e-learning intervention - Rosyady, Maulana; Karyanti, Mulya Rahma; Chozie, Novie Amelia (Paediatrica Indonesiana, 2025)
Background Antibiotic resistance is a global health threat. E-learning can be used to increase the knowledge of medical staff and the effectiveness of antibiotic use. Objective To evaluate the impact of e-learning intervention for pediatric doctors and residents on antibiotic use in pediatric patients. Methods This single-arm intervention study involved all pediatric doctors and residents from the Department of Child Health, Faculty of Medicine at Universitas Indonesia/Dr. Cipto Mangunkusumo Hospital (FMUI-CMH). Staff and residents underwent e-learning intervention on the topic of antimicrobial stewardship (AMS) via the E-learning Management System Universitas Indonesia (EMAS UI) website, followed by comparison of their pre- and post-intervention knowledge. The appropriate use of antibiotics pre- and post-intervention at October and December 2022, respectively, by was assessed by Gyssen's flowchart. Results A total of 135 (54.4%) antibiotic uses in the pre-intervention period and 170 (72.24%) in the post-intervention period were considered appropriate. A significantly greater proportion of subjects received appropriate antibiotic use after the intervention compared to before (95%CI 0.363 to 0.795; P=0.002). Forty-two out of 56 pediatricians and 119 out of 123 pediatric residents participated in the e-learning program. There was a significant improvement in knowledge levels between the pre- and post-intervention periods among pediatricians, with more passing the post-intervention assessment compared to the pre-intervention assessment (1 vs. 29, respectively; P=0.001). Similarly, a significant increase was observed among pediatric residents (10 vs. 66, respectively; P=0.001). Conclusion There was a significant increase in appropriate antibiotic use in pediatric patients at CMH after pediatric doctors and residents underwent e-learning interventions.